Small and Medium Enterprises in the Pandemic : Impact, Responses and the Role of Development Finance - Adian, Ikmal; Doumbia, Djeneba; Gregory, Neil; Ragoussis, Alexandros; Reddy, Aarti; Timmis, Jonathan (World Bank, Washington, DC, 2020)
This study highlights how COVID-19 has affected small and medium enterprises, drawing on newly released World Bank Enterprise Surveys in 13 countries. The study shows that firms of all sizes are severely affected in multiple dimensions; however, firm size matters for the intensity of the different channels of transmission and firms' responses. Small and medium enterprise sales shrink by more and their cash drains faster than large firms in the same sector and country. Among them, faster growing firms experience the demand shock somewhat less severely, but they are more exposed to international trade disruption, supply, and finance shocks. Yet, a range of firm responses to the downturn seem to be out of reach. Fewer small and medium-size enterprises, for example, start remote work, leaving their workers exposed to health risks. To make it through the pandemic, the majority of smaller firms do not turn to banks for loans; they need grants. Although development finance is not enough to fill the financing gap, development finance institutions are relevant -- in investment mobilization, demonstration, and know-how -- as economies move toward recovery and rebuilding. Delivering these requires rapid efforts to build partnerships and gather information in places where development finance has been limited in the past.